On the Relationship between PMSE Strength and Particle Precipitation - Antonsen, Tarjei; Havnes, Ove (European Space Agency, 2015)
Proc. ‘22nd ESA Symposium on European Rocket and Balloon Programmes and Related Research’, Tromsø, Norway, 7–12 June 2015 We have studied the relationship between particle precipitation and PMSE strength on days where we observe PMSE layers both with the EISCAT VHF and UHF radars. The UHF observations of the ionization and its variation, above the PMSE layer, is used as a measure of precipitation. Variations of the precipitation is compared with variations of the PMSE strengths observed with both radars. Although many cases apparently show a clear connection between precipitation and PMSE, where an increased precipitation leads to a strengthening of the PMSE, our findings confirm that there is no general and simple proportionality between the two. For the weakest PMSE there appears to be no correlation between precipitation and PMSE strength. For PMSEs around average strength of our observations there appears to be a weak positive correlation, which can be predicted by a timedependent dust cloud charge model. On some occasions an increased precipitation can, apparently, initially lead to an increase of PMSE strength which at some point starts to decline even if the precipitation continue to increase. This feature can also be seen in the results from the statistical analysis, however the number of occurrences is too low to conclude with significance and the time-dependent charge model described here does not reproduce such features. We have studied to what degree models for the PMSE scattering can explain the various cases of reaction of PMSE to changes in precipitation